PEMENUHAN HAK ANAK YANG DIPONDOKKAN DI PONDOK PESANTREN USIA DINI - Firman Agus Faisal; Abdullah Afif (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This article discusses the fulfillment of the rights of children who are boarded in early childhood Islamic boarding schools from the perspective of Islamic law and law. Early childhood Islamic boarding schools are Islamic boarding schools for children whose aim is to provide in-depth teaching of the Islamic religion from early childhood. This research is focused on digging deeper into the fulfillment of the rights of young children in boarding schools. It is important that special attention must be given to young children, especially in fulfilling children's rights in Islamic boarding schools.